Multibeam bathymetry raw data (Kongsberg EM 122 entire dataset) of RV METEOR during cruise M198 - Morelia Urlaub; Felix Gross; Alessandro Bonforte; Elisa Klein; Mia Schumacher (PANGAEA, 2024)
Raw multibeam bathymetry data were collected aboard RV METEOR during cruise M198 using a Kongsberg EM 122 multibeam echosounder. The expedition took place during 09.02.2024 - 22.02.2024 from Catania (Italy) to Catania (Italy) in the Mediterranean. The overarching aim was to (1) service the current seafloor deformation monitoring system and add long-term in-situ pore pressure and temperature measurements, (2) collect high-resolution bathymetric data with a multibeam echosounder mounted to an Autonomous Underwater Vehicle (AUV), (3) test a new generation of low-cost and easy-to-handle smart instruments (MOLA) for seafloor volcano monitoring, and (4) collect rocks with a chainbag dredge. Data were recorded within the EEZ of Italy. Sound velocity profiles (SVP) were applied on the data for calibration. Please see environmental data and the cruise report for details. The data are unprocessed and can therefore contain incorrect depth measurements (artifacts) if not further processed. Note that refraction errors may occur when no proper SVP is applied. Acquisition and provision of the data are part of the DAM Underway Project and published according to the FAIR principles.